National collective identity in transitional societies: Salience and relations to life satisfaction for youth in South Africa, Albania, Bulgaria, the Czech Republic, Kosovo and Romania. Issue 2 (24th April 2017) - Dimitrova, Radosveta; Musso, Pasquale; Naudé, Luzelle; Zahaj, Skerdi; Solcova, Iva Polackova; Stefenel, Delia; Uka, Fitim; Jordanov, Venzislav; Jordanov, Evgeni; Tavel, Peter
Abstract : In this study we investigated the salience of the construct of national collective identity and its associations with life satisfaction among adolescents living in transitional societies characterised by relevant change in the last decades. Participants were 1 066 adolescents ( M = 15.35 years, SD = 1.35) from South Africa ( n = 186) and five Central Eastern European countries, including Albania ( n = 209), Bulgaria ( n = 146), Czech Republic ( n = 306), Kosovo ( n = 116), and Romania ( n = 103). They completed a questionnaire including national identity and life satisfaction scales. Data were analysed using confirmatory factor analysis and multi-group structural equation modeling. Results showed that national identity of adolescents in transitional societies is multidimensional and pertains to different salient dimensions (i.e., self-categorisation, evaluation, importance, attachment, and behavioural involvement). Importantly, the findings provided evidence to suggest that higher levels of national collective identity are associated with increased levels of life satisfaction.